A cross sectional study of coagulation profile in term normotensive pregnancy and hypertensive disorders like preeclampsia, eclampsia - Priya, Madana Jyotsna; Ethiraj, Gomathy; Rangappa, Sheela Shivamonga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Normal pregnancy is a procoagulant state. In preeclampsia, this process of coagulation is exaggerated and will lead to further effects on the mother, placenta and fetus. The purpose of this study is to find out the changes that occur in the coagulation indices in pregnancy induced hypertension as compared to that in normal pregnancy which will help in the better management of patients with pregnancy induced Hypertension. Methods: This was a cross sectional study in 116 patients with normotensive and patients with hypertensive disorders in pregnancy conducted in a tertiary medical facility. Coagulation parameters like platelet count, prothrombin time, activated partial thromboplastin time, bleeding time and clotting time were evaluated. We used the difference of 5% in mean PT between normotensive (control) and hypertensive patients by applying 80% power and alpha error of 5%. Results: Platelet counts of study population were significantly related to the prognosis of the patient. The cut off values of major parameters like aPtt, BT with the outcome were with p value of 0.37 and 0.76 respectively. Conclusions: In cases of pregnant complicated with HDP, parameters like coagulation profile, bleeding time, clotting time were probably useful indicators in the early diagnosis and management of severe morbidity of the mother and the fetus. Further prospective trials with large study population are warranted to evident these results.